In-utero transfer of decidualized endometrial stromal cells increases the frequency of regulatory T cells and normalizes the abortion rate in the CBA/J × DBA/2 abortion model - Zarnani, Kayhan; Zarnani, Kimia; Maslehat-Lay, Nasim; Zeynali, Bahman; Vafaei, Sedigheh; Shokri, Mohammad-Reza; Vanaki, Negar; Soltanghoraee, Haleh; Mirzadegan, Ebrahim; Edalatkhah, Haleh; Naderi, Mohammad-Mehdi; Sarvari, Ali; et al. (Frontiers in Immunology, 2024)
Introduction: Failure to adequate decidualization leads to adverse pregnancy outcomes including pregnancy loss. Although there are plenty of reports underscoring immune dysfunction as the main cause of abortion in CBA/J females mated with DBA/2 males (CBA/J x DBA/2), little is known about the potential role of impaired endometrial decidualization. Methods: Endometrial stromal cells (ESCs) from CBA/J mice were in vitro decidualized and the proteome profile of secrotome was investigated by membrane-based array. CBA/J mice were perfused in utero with either decidualized ESCs (CxD/D), undecidualized ESCs (CxD/ND), or PBS (CxD/P) 12 days before mating with DBA/2 males. Control mice were not manipulated and were mated with male DBA/2 (CxD) or Balb/c (CxB) mice. At day 13.5 of pregnancy, reproductive parameters were measured. In vivo tracking of EdU-labeled ESCs was performed by fluorescence microscopy. Frequency of Tregs in paraaortic/renal and inguinal lymph nodes was measured by flow cytometry. Proliferation of pregnant CBA/J splenocytes in response to stimulation with either DBA/2 splenocytes was assessed by 5,6-carboxyfluorescein diacetate succinimidyl ester (CFSE) flow cytometry. Results: In CxD/D mice, the resorption rate was reduced to match that seen in the CxB group. Intrauterine perfused ESCs appeared in uterine stroma after 2 days, which remained there for at least 12 days. There was no difference in the number of implantation sites and embryo weight across all groups. The frequency of regulatory T cells (Treg) in the inguinal lymph nodes was similar across all groups, but it increased in the paraaortic/renal lymph nodes of CxD/D mice to the level found in CxB mice. No significant changes were observed in proliferation of splenocytes from pregnant CxD/D compared to those of CxD group in response to stimulation with DBA/2 spelnocytes. Decidualization of ESCs was associated with a profound alteration in ESC secretome exemplified by alteration in proteins involved in extracellular matrix (ECM) remodeling, response to inflammation, senescence and